Flexibility and hand–eye coordination profiles in children aged 10–12 years - Masnur Ali; Qory Jumrotul Aqobah; Ubaedi Ubaedi (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
The development of physical and motor abilities in school-age children plays an essential role in supporting optimal growth and development. This study aimed to determine the profile of flexibility and hand–eye coordination among children aged 10–12 years in the coastal area of Anyer, Banten. This study employed a quantitative descriptive method using a survey approach. The population consisted of children aged 10–12 years living in the coastal area of Anyer, Banten. The sample included 43 children, consisting of 24 girls and 19 boys, selected using purposive sampling techniques. The instruments used were the sit and reach test to measure flexibility and the ball throw-and-catch test to measure hand–eye coordination. Data were analyzed using descriptive statistics in the form of frequencies and percentages. The results showed that the flexibility level of children aged 10–12 years was predominantly categorized as very good, with 27 children (62.79%), followed by good with 11 children (25.58%) and moderate with 5 children (11.62%). In contrast, the hand–eye coordination test revealed that 25 children (58.14%) were categorized as poor, 13 children (30.23%) as moderate, 3 children (6.98%) as very poor, and only 2 children (4.65%) as good. The findings indicate that children living in the coastal area of Anyer generally demonstrate excellent flexibility; however, their hand–eye coordination ability remains relatively low. Therefore, physical education programs should provide more structured visual–motor coordination activities through manipulative games and sports activities to improve children’s motor development.